The Jack mackerel Trachurus murphyi and the environmental macro-scale variables - Espino, Marco (2013)
This paper analyses information on various macro environmental variables available since 1876 for the Southeast Pacific and more recent data on Jack mackerel Trachurus murphyi (Nichols, 1920) landings and biomass in the Peruvian sea, relating them to probable areas of water masses equivalent to Cold Coastal Waters (CCW) and Subtropical Surface Waters (SSW). It is concluded that the index of the Pacific Decadal Oscillation (PDO) presents expressions of variability that are consistent with those found for the Southern Oscillation Index (SOI) and that the detected changes in biomass of Jack mackerel T. murphyiin the Peruvian sea reflect changes in the availability of the fish stock associated with secular (SOI) and decadal (PDO) variability patterns. These fluctuations in stock availability impact fisheries in Ecuador, Peru and northern Chile, which show significant variations in their landings and would have given a biased picture of the state of abundance, leading to wrong diagnoses of the real situation of the exploited stocks. These patterns of variability would also affect the appearance of El Niño, making them start in the southern hemisphere autumn or spring depending on whether the current PDO is positive or negative. Periods of high (1876 – 1925 and 1976 – 2012) and low (1926 – 1975) variability are also identified in relation to the Euclidean distance of the variances of the SOI; and in relation to the PDO a distinction is made between warm (1925 – 1944 and 1975 – 1994), cold (1945 – 1974) and tempered or interface periods (1895 – 1924 and 1995 – 2012), the latter being explained by the interaction between periods of high variability.